Prototipe Sistem Informasi Perpustakaan Pusat dan Daerah - Intanny, Vieka Aprilya; Santosa, Paulus Insap; Kadir, Abdul (Universitas Atma Jaya Yogyakarta, 2015)
Abstract. Library has one of important resources to obtain information for research needs. The quality of a library information system needs to improve promptly because the information is needed quickly and accurately. In order to present library catalogue data that can be integrated with all central and local libraries, the library information system of Research and Development of the Human Resources Agency of the Ministry of Communication and Information Technology (Balitbang SDM Kominfo) needs to be well developed. The aim of this research is to design a prototype of library information system in order to present library data from central and local libraries accurately. Simulation tests are performed in eight research centers in the Ministry of Communication and Information Technology. The test is performed to analyze the perception of the users about the effectiveness of the system. The results show that the central library and information systems have good quality. Keywords: central library, local library, prototype, information systemÃ‚Â Abstrak. Perpustakaan merupakan sarana untuk mendapatkan literasi informasi melalui hasil penelitian yang telah dilakukan. Peningkatan kualitas layanan sistem informasi perpustakaan yang tersaji dengan cepat, akurat dan aktual mutlak diperlukan. Untuk itu dipandang perlu suatu perbaikan sistem perpustakaan Balitbang SDM Kominfo agar dapat menyajikan data perpustakaan yang dapat terintegrasi antara perpustakaan pusat dan perpustakaan daerah. Penelitian ini bertujuan untuk merancang prototipe suatu sistem informasi perpustakaan pusat dan daerah agar data perpustakaan pusat dan daerah dapat tersaji dengan cepat dan akurat. Pengujian dilakukan dengan simulasi sistem di delapan balai Kominfo. Pengujian ini bertujuan untuk menganalisis persepsi administrator pusat dan administrator daerah mengenai efektivitas sistem. Hasil pengujian menunjukkan bahwa sistem informasi perpustakaan pusat dan daerah memiliki kualitas yang baik. Kata Kunci: perpustakaan daerah, perpustakaan pusat, prototipe, sistem informasi